2019
DOI: 10.1038/s41598-018-37109-1
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Gratitude Moderates the Association between Socioeconomic Status and Interleukin-6

Abstract: Socioeconomic disparities in health are prevalent and growing in importance as a concern among academics, policymakers, and the general public. However, psychological resources that can narrow such disparities have not been well-examined. The current study examined the moderating role of dispositional gratitude in the relationship between socioeconomic status (SES) and inflammation risk as an index of health. Participants consisted of 1,054 midlife adults from the biomarker project of the Midlife in the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
0
20
1
Order By: Relevance
“…The present finding allows us to identify a significant boundary condition around the potential benefits of the experience of gratitude. Despite previous findings consistently demonstrating the association between gratitude and both physical and socioemotional well-being [20,71,72], the present study indicates that the benefits of gratitude may not apply across all domains in life. It may be argued that gratitude does not confer benefits on higher-order cognitive performance, such as cognitive flexibility.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present finding allows us to identify a significant boundary condition around the potential benefits of the experience of gratitude. Despite previous findings consistently demonstrating the association between gratitude and both physical and socioemotional well-being [20,71,72], the present study indicates that the benefits of gratitude may not apply across all domains in life. It may be argued that gratitude does not confer benefits on higher-order cognitive performance, such as cognitive flexibility.…”
Section: Discussioncontrasting
confidence: 99%
“…Another recent study by Ksenofontov and Becker [64] reported that expressing gratitude to high-power groups that had committed an offence resulted in less protest behaviors in low-power groups. Although gratitude has been consistently linked with socioemotional and health benefits [20,23,65], the current study contributes to the literature by demonstrating that the practice of gratitude may not always be advantageous, especially in the domain of cognitive flexibility.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, prior studies have revealed that a grateful attitude is negatively correlated with harmful psychological tendencies such as avoidance and revenge motivations (Szcześniak and Soares, 2011). Hartanto et al (2019) found that higher trait gratitude weakens the negative effect of socioeconomic status on health outcomes. Such empirical investigations hold a variety of practical implications in research as well as clinical settings.…”
Section: Conceptualizing Dispositional Gratitudementioning
confidence: 99%
“…Fewer studies have explored the bidirectional links between positive affect and levels of inflammation, especially as they relate to neural functioning. This paucity of work is surprising, considering that several studies have found that both dispositional positive affect ( Marsland et al., 2006 ; Stellar et al., 2015 ; Hartanto et al., 2019 ) and momentary positive affective states ( Steptoe et al., 2005 ) are associated with lower levels of inflammation. To date, no known neuroimaging studies have examined the efferent pathway or how the induction of a positive affective experience influences levels of inflammation.…”
mentioning
confidence: 99%